GARDENS CREATED BY KOKAND KHANATES - Gulomjonovna, Nazarova Nodira; Khabibullaevna, Matkarimova Barno; Sobirjonovna, Madrakhimova Mahbuba; Djakhonobodkhonovna, Khodjayeva Guzal; Bakhtiyarovna, Yagyaeva Elvina (International Journal of Psychosocial Rehabilitation, 2020)
: Even in ancient times, the whole world recognized that Turan, Maverannahr, Turkestan, the territory that we now call Uzbekistan, i.e. our father’s home, is one of the cradles of not only eastern, but also global civilization. In those days, wealthy people, owners of large property, officials, and merchants created various structures at their own expense like gardens, madrassas, mosques, bridges. Kokand city which is located in south-western part of Fergana valley is one of the cities of cultural and historical significance. This holy land gave the world great thinkers, scholars, politicians, generals. The first manuscripts date back to the X century. The city has a rich history for centuries. This article describes the role and significance of gardens in Kokand Khanets. The essence of gardens of impact to the development of khanates is also disclosed. This article encourages foreign tourists and natives to learn and stay informed. In particular, the importance of historical places is emphasized. The article reveals that historical gardens entirely and powerfully motivate tourists for achievement of historical attitude and practices. • The Constitution of the Republic of - Tashkent: Uzbekistan, 2014. • Karimov I. A. Uzbekistan at the Threshold of the 21st Century: Threats to Security, Conditions for Stability, and Guarantees of Progress. // For Security and Sustainable Development: T. 6. - T .: Uzbekistan, 1998. • Karimov I. A. There is no future without historical memory. // We build our future with our own hands. T. 7. - T .: Uzbekistan, 1999. • Karimov A. High spirituality is an invincible force. - T .: "Spirituality", 2008. - 176 p. • Anarbaev Axxentent - Desktop Drevney Fergany. - T .: Tafakkur, 2013, 536 p. • Askarov A. History of Uzbekistan. - Tashkent: "Teacher", 1994. • Askarov A. A., Matboboev B. The ancient roots of farming. - Tashkent: Journal of Science and Life, 1985, Issue 1 • Bulatov S. Uzbek folk applied art. - Tashkent: Labor, 1991. • Zasypkin N. Architecture Pamyatniki Fergany. - M.: Iskusvo Vostoka, 1930. • Zakhiriddin Muhammad Babur. - T .: Star, 1989. - 368 p. • Zohidov Sh The World of Architects. - Tashkent: Editorial Board of Commons, 1996. • Isakov B. Asiruddin Ahsikati is our great compatriot. // "History and destiny: Problems of the study of the history of the Fergana Valley". Materials of Republican scientific-practical conference. Book 2, November 23 - 24, 2000. - Namangan, 2002, pp. 100 - 104. • Isaacov Ancient foci of civilization. // Express Info, 11, 18, 25 August 2005. • Isaacov B. Responsibility to Possession. ―Listing‖ section (to the 70th anniversary of the birth of academician A. Askarov). // The Wreath of Ma’rifat, October 6, 2005. • Isaacov B. «The mother of Fergana cities». "Look at the Maze". // Express Info, 2006, 2, 9, 16, 23, March 30, 6, 13, 20, April 27, 4, 11, 18, 25 May, 1, 8, 15 June. • Qosimov Ancient Fergana Secrets. - Namangan: Udarnik, 1992. • Soriev The Land of the World. U. Soriev.Man and the Law.2010. N52.53. • Madiyorov B. He was a world traveler. B. Madiyorov. The truth of Fergana.2011. N79. C. 3. 19.Makhmudov Spacious mansions in the Sulim Valley. M. Mahmudov. Society. 2014. N28. C. 11. 20.Polvonova K. Charming Fergana. K. Polvonova. The truth of Fergana. 2013. N73. C. 3 21.Polvonova K. Fergana is in full swing. K. Polvonova. The truth of Fergana.2013. N78. C. 3. • Nazarova , Madrakhimova M. Peculiarities of using shrines in Fergana Valley for the Purpose of Tourism. International journal on economics, finance and sustainable development. 2019, 1-4p. • Kokand khanates // Encyclopedic dictionary of Brochazium and Ephrone: 86 t. (82 t. and 4 ). — SPB., 1890—1907. • Nalivkin P. A brief history of Kokand Khanates. Kazan, 1886, 127 p. • Sichot The book of dynasties. — М.: «AST», «East-west», 2005 — (Series of Historical library). — 959 • ISBN 5-17-032495-2 (ООО «AST publishing»),ISBN 5-478-00092-2 (ООО «East-west») • Bulgakov A.I., Shumov S.A., Andreyev A.R. “The history of Central Asia”. Historical books collection/ — М.: «Eurolins», «Russian panorama», 2003 — («History of countries and people» series). — 504 p, 237 lib. ISBN 5-93165-072-5